Effect of Drying on the Yield and Sensory of Germinated Mung Bean Flour (Vigna radiata L) - Sudana Fatahillah Pasaribu; Herviana Herviana; Wanda Lestari (Universitas Darussalam Gontor, 2023)
Background: Mung bean (Vigna radiata L.) is a source of nutrient-rich vegetable protein and provides many health benefits. The germination process is one way to increase the bioavailability of mung beans. Objective: This study aims to determine the effect of drying time on the characteristics and the best drying time on germinated mung bean flour. Method: This study used a one-factor design, namely drying time (7 hours, 10 hours, and 13 hours) with yield and sensory parameters (aroma, color, and texture) of germinated mung bean flour. All data were tested with ANOVA and continued with Duncan's LSD test. Results: The results showed that there was an effect of drying time on the yield value, aroma, and texture of germinated mung bean flour (p<0.01). However, there was no effect of drying time on the aroma germinated mung bean flour P1 (7 hours), P2 (10 hours), dan P3 (13 hours) (p>0.01). Conclusion: The conclusion of this study proves that the drying time of P1, P2, and P3 can affect the increase in yield values and sensory scores (color and texture) on germinated mung bean flour. However, the drying time of P1, P2, and P3 did not affect sensory (aroma). The best germinated mung bean flour is dried for 13 hours at 55˚C. Key words : Drying, Germinated Mung Been Flour, Yield, Sensory